New records of Eutardigrada from Belarus with the description of three new species - Pilato, Giovanni; Kiosya, Yevgen; Lisi, Oscar; Sabella, Giorgio (Zootaxa, 2012)
The list of tardigrade species recorded from Belarus is provided; nine were new records for this geographic area and three,Macrobiotus sottilei sp. nov., Paramacrobiotus klymenki sp. nov. and Hypsibius valentinae sp. nov. were new to science.Macrobiotus sottilei sp. nov. had smooth cuticle; eye spots present; the dorsal transverse ridges of the buccal armaturejoined to form a continuous arc; pharyngeal bulb with two macroplacoids and microplacoid; eggs with processes in shapeof inverted goblets with indented distal discs; egg shell with a very dense reticular design.Paramacrobiotus klymenki sp. nov. had smooth cuticle; eye spots absent; buccal armature similar to that of P. areolatus;buccal tube not very wide; stylet supports inserted on the buccal tube at about 80% of its length; pharyngeal bulb withthree macroplacoids; microplacoid absent; eggs with conical processes with a reticular design similar to that of P. areola-tus; egg shell areolated; central area of each areola slightly thickened but not subdivided.Hypsibius valentinae sp. nov. had smooth cuticle; eye spots present; buccal tube very narrow; pharyngeal bulb with twomacroplacoids and a small septulum, claws of the Hypsibius type; small, smooth, flexible lunules present; a short cuticular bar is present between the bases of the claws of the hind legs; no cuticular bar on the first three pairs of legs.